Atomic layer deposition of ruthenium at 100 °C using the RuO4-precursor and H2. Issue 1 (10th November 2014) - Minjauw, Matthias M.; Dendooven, Jolien; Capon, Boris; Schaekers, Marc; Detavernier, Christophe
Abstract : A novel Ru ALD process at 100 °C using the inorganic RuO4 -precursor in a reduction chemistry with H2 is being reported, and a proposal for the underlying reaction mechanism is given. Abstract : In this paper we report a low temperature (100 °C) ALD process for Ru using the RuO4 -precursor (ToRuS™) and H2 as the reactant. The thermal decomposition behaviour of the precursor in the range of 50 °C–250 °C was investigated and it was found that thermal decomposition of RuO4 to RuO2 starts at a sample temperature of 125 °C. The RuO4 /H2 process (0.0045 mbar/4 mbar) was attempted at temperatures below this decomposition limit and it was found that ALD growth of pure Ru is possible in a narrow temperature window near 100 °C. The growth rate during steady state growth was found to be 0.1 nm per cycle. The Ru film nucleated easily on a wide range of substrates (H-terminated Si, TiN, Pt and Al2 O3 ). Although the films are grown at a low temperature, they are considerably pure and are of good quality as evidenced by a resistivity of 18 μΩ cm for an 18 nm film and a relative atomic concentration of impurities <5% as determined by XPS. It is hypothesized that the reaction of the RuO4 molecule with the Ru-surface leading to a monolayer of RuO2 is the mechanism that ensures a self-saturated behaviour of the first half reaction, which is a critical requirement to achieve a well-behaved ALD process.